"Think small first in the EU"? A Reality Check. (March 2014) - Typhaine Beaupérin,
Abstract : Despite recent efforts by the European Commission to improve the application of the SME test by its services, EUROCHAMBRES 2013 SME Test Benchmark reveals that the Commission is still, in the majority of the dossiers analysed, failing to 'think small first' and take into account the costs and benefits to smaller businesses in the preparation of legislative proposals.